2023
DOI: 10.1111/1462-2920.16427
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence that lignin‐modifying enzymes are essential for degrading plant cell wall lignin byPleurotus ostreatususingCRISPR/Cas9

Takehito Nakazawa,
Iori Yamaguchi,
Yufan Zhang
et al.

Abstract: Lignin‐modifying enzymes (LMEs), which include laccases (Lacs), manganese peroxidases (MnPs), versatile peroxidases (VPs), and lignin peroxidases (LiPs), have been considered key factors in lignin degradation by white‐rot fungi because they oxidize lignin model compounds and depolymerize synthetic lignin in vitro. However, it remains unclear whether these enzymes are essential/important in the actual degradation of natural lignin in plant cell walls. To address this long‐standing issue, we examined the lignin‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…This is highly indicative of an adaptive, rather than inductive, response of the fungus to the growth niche. This concept, shown here along the three-week sampling period, is in high agreement with the recent analysis described by Nakazawa et al [38] and warrants a future emphasis on deciphering the kinetics of the substrate utilization process. In addition to the marked temporal changes observed in the measured transcriptional profiles, further analyses using WGCNA [43], which has been previously used to identify genes associated with sporulation processes in Ganoderma lingzhi [44] and for discovering the landmark genes involved in mushroom development and the evolution of complex multicellularity [45], we were able to identify key modules of genes highly associated with the ssp knock-down genotype (Figures 7 and 8).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is highly indicative of an adaptive, rather than inductive, response of the fungus to the growth niche. This concept, shown here along the three-week sampling period, is in high agreement with the recent analysis described by Nakazawa et al [38] and warrants a future emphasis on deciphering the kinetics of the substrate utilization process. In addition to the marked temporal changes observed in the measured transcriptional profiles, further analyses using WGCNA [43], which has been previously used to identify genes associated with sporulation processes in Ganoderma lingzhi [44] and for discovering the landmark genes involved in mushroom development and the evolution of complex multicellularity [45], we were able to identify key modules of genes highly associated with the ssp knock-down genotype (Figures 7 and 8).…”
Section: Discussionsupporting
confidence: 91%
“…Considering the recently proven redundancy of some components of the lignin-degrading machinery [37], it is likely that these are preferentially involved in lignin degradation under varying circumstances. Recently, using multiple mnp/vp/lac mutants of P. ostreatus, Nakazawa et al [38] demonstrated that MnPs and VPs have overlapping roles in the degradation of natural lignin.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple gene disruption with CRISPR/Cas9 may overcome this problem. For example, by creating a sextuple disruption strain for lignin-modifying enzyme (LME)-encoding genes, the crucial role of LMEs in lignin degradation by P. ostreatus was demonstrated (Nakazawa et al 2023b ; see below).…”
Section: Genetic Toolbox For P Ostreatusmentioning
confidence: 99%
“…Additionally, one laccase-encoding gene, lac2 , was disrupted because its transcript accumulation was high when grown on beech wood sawdust medium supplemented with wheat bran (BWS; Wu et al 2020 ). Lignin-degrading abilities were mostly lost in the vp2 / vp3 / mnp3 / mnp6 / mnp2/lac2 sextuple-gene disruptants but not in the vp2 / vp3 / mnp3 / mnp6 / mnp2 and vp2 / vp3 / mnp3 / mnp6 / lac2 quintuple-gene disruptants grown on BWS, clearly showing their essential role (Nakazawa et al 2023b ). This is the first experimental evidence indicating that these LMEs play essential roles in wood lignin biodegradation by white-rot fungi.…”
Section: Wood Degradationmentioning
confidence: 99%